2021
DOI: 10.1016/j.aca.2021.338259
|View full text |Cite
|
Sign up to set email alerts
|

Deep mining of oxysterols and cholestenoic acids in human plasma and cerebrospinal fluid: Quantification using isotope dilution mass spectrometry

Abstract: Both plasma and cerebrospinal fluid (CSF) are rich in cholesterol and its metabolites. Here we describe in detail a methodology for the identification and quantification of multiple sterols including oxysterols and sterol-acids found in these fluids. The method is translatable to any laboratory with access to liquid chromatography – tandem mass spectrometry. The method exploits isotope-dilution mass spectrometry for absolute quantification of target metabolites. The method is applicable for semi-quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(70 citation statements)
references
References 58 publications
1
60
0
Order By: Relevance
“…Cholesterol accumulation in the interior of the compartment was reasoned to mediate the anti-viral activity of both 25-HC and ICZ (14). A complication to this mechanism is that in cellular assays 25-HC travels directly to the endoplasmic reticulum without traversing the lysosome on its way to inhibiting SREBP-2 processing (34,112), however, in vivo it is likely that when derived from the circulation, where the majority of 25-HC is esterified (113,114), the ester as part of lipoprotein particles is taken-up by receptor mediated endocytosis and travels to the lysosome where it is hydrolysed to the non-esterified molecule. Zang et al concluded that 25-HC reduces SARS-CoV-2 spike-mediated fusion via a mechanism which involves altered cholesterol levels leading to inhibition of viral replication (14) (115,116).…”
Section: -Hc and Coronavirusesmentioning
confidence: 99%
See 3 more Smart Citations
“…Cholesterol accumulation in the interior of the compartment was reasoned to mediate the anti-viral activity of both 25-HC and ICZ (14). A complication to this mechanism is that in cellular assays 25-HC travels directly to the endoplasmic reticulum without traversing the lysosome on its way to inhibiting SREBP-2 processing (34,112), however, in vivo it is likely that when derived from the circulation, where the majority of 25-HC is esterified (113,114), the ester as part of lipoprotein particles is taken-up by receptor mediated endocytosis and travels to the lysosome where it is hydrolysed to the non-esterified molecule. Zang et al concluded that 25-HC reduces SARS-CoV-2 spike-mediated fusion via a mechanism which involves altered cholesterol levels leading to inhibition of viral replication (14) (115,116).…”
Section: -Hc and Coronavirusesmentioning
confidence: 99%
“…Interestingly, these results were not replicated in a mouse model of NASH where levels of 7α,26-diHC and 7α,26-diHCO were about 25 ng/g and 50 ng/g, respectively, in both WT and treated animals (131). It is important to note that both 7α,26-diHC and 7α,26-diHCO are found in man and mouse as 25Rand 25S-epimers where the stereochemistry at C-25 is different (113,132), and that Raselli specifically quantified the 25R-epimer (131). Very few other studies define the specific epimer(s) measured, however, the 25R-epimers is usually dominant except in the case of CYP27A1 deficiency (113,132,133), where the 25S-epimer dominates.…”
Section: α25-dihc 7α26-dihc Enzymes and Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since GP can label sterols with a carbonyl group, the sterols with a hydroxyl group and oxysterols with a carbonyl group cannot be analyzed in a single LC-MS analysis using GP derivatization. However, GP/d 5 -GP can be used to quantify oxysterols and sterols simultaneously if sterols are oxidized by cholesterol oxidase (COD) first to contain a carbonyl group (Scheme 3) [137]. On the basis of this principle, it is possible to quantify up to four different samples in a single run by using differential mass tags and isobaric mass tags simultaneously through multiplex methods [138].…”
Section: Absolute Quantificationmentioning
confidence: 99%